CHARACTERISTICS OF DECORATIVE MOTIFS AND FUNCTIONS OF TRADITIONAL SILUNGKANG WOVEN FABRIC IN SAWAHLUNTO CITY IN THE CONTEXT OF MINANGKABAU CULTURE - Prihatin, Purwo; Sunarmi; Andar Indra Sastra (Proceeding of International Conference on Art, Media, and Culture (ICAMAC), 2024)
Traditional Silungkang woven fabric is a rich and valuable cultural heritage of the Minangkabau people in West Sumatra, Indonesia. Silungkang woven fabric is passed down through generations, taught from one generation to the next, ensuring its preservation to this day. The purpose of this paper is to describe and analyze the decorative motifs on traditional Silungkang woven fabric, as well as to reveal the cultural, aesthetic, and local wisdom values of the Minangkabau people contained within it.            Through an aesthetic approach, including data collection from literature studies, observations, documentation, and interviews, as well as data analysis, it is concluded that the weaving is not just a piece of cloth but also a reflection of the beauty, skill, and local wisdom of its people. The decorative motifs found in Silungkang woven fabric reflect the harmony between nature, daily life, and the cultural values of the Minangkabau community. Characterized by geometric patterns and rich colors, each piece of woven fabric becomes a unique and distinctive work of art. The decorative motifs used in Silungkang woven fabric depict symbols of life, nature, religion, and Minangkabau cultural customs, thus representing traditional cultural values in line with the Minangkabau philosophy "alam takambang jadi guru" (nature as the teacher). The traditional Silungkang woven fabric motifs are categorized into three groups: motifs named after flora, fauna, and natural objects, which form the cultural identity of the Minangkabau. Flora motifs include patterns like bamboo shoots and mangosteen buds, fauna motifs such as "itiak pulang patang" (ducks going home in the evening) and "bada mudiak" (fish swimming upstream), and natural object motifs such as the traditional house (rumah gadang), rice barns (rangkiang), stars, and so on. Each decorative motif on Silungkang woven fabric possesses characteristics, beauty, finesse, and meaning within the Minangkabau cultural context. Silungkang woven fabric, as a cultural heritage of the Minangkabau people, serves both traditional and commercial.